Assessing the tolerance of three species of Quercus L. and Iowa grown Betula nigra L. provenances to foliar chlorosis in elevated pH substrate - Hoch, Braden Keith (Kansas State University, 2018)
Oak trees (Quercus L.) and river birch (Betula nigra L.) are two horticulturally significant crops widely used in landscapes but notorious for developing iron (Fe) induced interveinal foliar chlorosis (IFC) in alkaline soils. Variation in IFC has been observed between species of oak and provenances of river birch suggesting that species and provenances endemic to alkaline soils do not always display this chlorosis. Limited studies investigating the effect of elevated pH on oak and river birch have been conducted. More environmentally tolerant and aesthetically pleasing selections could be used if they are first screened to determine their adaptability to high pH soils. Three experiments were conducted to evaluate Texas red oak (Quercus buckleyi Nixon and Dorr) and Durand oak [Quercus sinuata Walter var. breviloba (Torr.) C.H. Mull.] with landscape collections of pin oak (Quercus palustris L.) to determine the extent of IFC when grown at elevated pH. When grown in an elevated pH substrate, pin oak was unable to maintain elevated leaf total leaf Fe concentrations, consistently developed IFC, and exhibited low total leaf chlorophyll concentrations compared to non-chlorotic pin oak seedlings in the control pH substrate. Texas red oak and Durand in the elevated substrate did not develop IFC and maintained high leaf chlorophyll concentrations compared to controls; they also sequestered greater amounts of substrate Fe in leaves compared to pin oak in the elevated substrates. Another crop of ornamental significance and widely planted in the landscape, river birch (Betula nigra L.), develops IFC in high pH soils. Two experiments evaluated river open- pollinated (OP) seedlings of Iowa provenances, OP ‘BNMTF, and clones from selected Iowa provenances, ‘BNMTF’, ‘Cully’ in an elevated pH substrate. A seed source from Bearbower Sand Prairie, Buchanan Co., IA (BSP3) had greater leaf chlorophyll than ‘BNMTF’OP, and a clone from Clemons Creek WMA, Washington Co., IA (CCWMA3) than the trade standard ‘Cully’. Although differences in total leaf chlorophyll were observed, all sources in elevated pH substrate did not sequester sufficient amounts of leaf Fe compared to their controls. Field evaluations with considerations of provenance performance in different hardiness zones should be used to determine the potential of these Iowa sources as more suitable selections for use in landscapes with alkaline soils.
Keywords: Chlorosis; pH; Quercus betulaIron deficiency